The Role of Artificial Intelligence in Developing Future Learning Skills from the Perspective of Faculty Members in Syrian Universities (Latakia University (formerly Tishreen) Journal for Research and Scientific Studies - Arts Humanities Series, 2025)
This study aimed to explore the role of artificial intelligence (AI) in developing future learning skills from the perspective of faculty members in Syrian universities. The study sample included 365 faculty members from Syrian major universities. Data were collected using an electronic questionnaire distributed via Google Forms. The questionnaire addressed the extent to which AI contributes to enhancing skills such as creativity, innovation, critical thinking, problem-solving, and other future learning skills. The results revealed that AI contribute on fostering future learning skills positively by encouraging students to think outside the box, providing tools that allow students to experiment with innovative solutions to educational problems, supporting the development of creative projects and research, and enhancing the application of knowledge in innovative ways. The study concluded the necessity of integrating AI technologies effectively into university education, training faculty members on how to employ these technologies efficiently, and providing the necessary infrastructure to activate AI's role in developing future learning skills in line with modern educational challenges and demands.
Keywords: Artificial Intelligence, future learning skills, faculty members, creativity and innovation.